A REVIEW ON INFLAMMATORY BOWEL DISEASE - DESHMUKH, CHINMAY DEVIDAS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
The gastrointestinal tract commonly known as the digestive tract is one of the most important canals in the body. It consists of the passage from mouth to anus including organs that help in the digestion. The food is taken into the mouth and all essential nutrients, and vitamins are absorbed from the digestive tract. The tract consists of important digestive organs such as the pharynx, esophagus, stomach, intestine, and rectum. Although the word gastrointestinal includes the entire tract, most commonly it is the stomach and intestine. The process of digestion is complex including a variety of minor processes. This includes mastication of food, mixing with saliva to form a bolus, mixing with various gastric enzymes to form chyme, mixing with intestinal, pancreatic and hepatic juices, absorption, and extraction, removal of water and fecal compaction and elimination. These processes are very disciplined, round-the-clock, and systematic. However, there may be chances of certain problems in this routine work such as infections, inflammation, irritation, acidity, or diseases. Constipation, diarrhea, inflammatory bowel disease (IBD), fissure, piles, fistulas, and hemorrhoids are some of the common. The smooth and easy process of digestion of food and elimination of waste is disturbed due to any of these diseases. Certain environmental factors, genetics, gender and age, smoking, chair syndrome, and geographical factors are the main things of the development of IBD. IBD causes prolonged digestive tract inflammation. There are various other underlying symptoms of the disease which are discussed in the article. The two types of this disease are ulcerative colitis and Crohn’s disease. There are possible complications of these diseases such as malnutrition, weight loss, colon cancer, fistula, perforation, bowel rupture, etc. If these are not managed well in advance, then it may lead to the death of the person. To know more about the disease, the present review is an attempt to focus on all possible causes, clinical presentation, diagnosis, complications, and management of IBD. The experimental induction models are also tried to discuss in the present article.